2022-RA-1518-ESGO Role of Plastic surgery following resection of vulval tumours: Is collaboration the key?. (20th October 2022) - Singhal, Maneesh; Singhal, Seema; Chauhan, Shashank; Dash, Suvashis; Dash, Suvashis; Saha, Shivangi; Chandrasekar, Shruthi; Singh, Nandini; Mandal, Amit; Singh, Anju; Malhotra, Neena; Bhatla, Neerja
Abstract : Introduction/Background: Reconstruction of the vulva following extirpative surgeries is essential in restoring the form and functions of daily living. Complex defect reconstruction can be difficult and may necessitate collaboration between gynaecology and reconstructive surgeons. We present our experience in the reconstruction of vulval defects following tumour excision (benign and malignant) and in the management of post inguinal lymph node dissection (ILND) lymphorroea. Methodology: A prospective study was conducted between 2020–2022. All patients (N=8) requiring plastic surgical intervention were included. Five patients with vulval tumours underwent reconstruction. Three patients having ILND lymphorrhoea and other malignant vulval tumours were managed conservatively with low pressure negative wound therapy (NPWT). Results: The median age was 50.4 years (28–63 years), requiring a mean hospital stay of 13.6 days. Two cases of vulval squamous cell carcinoma underwent local V-Y advancement flap and a pedicled anterolateral thigh flap, respectively. One case of primary vulval lymphedema was managed with debulking and reconstruction of the labia majora and minora with vulval flaps. Two benign tumours of the vulva (fibromatosis) required W-plasty and V-Y advancement flap respectively.One patient had vaginal wall necrosis and partial flap dehiscence in the immediate post-operative period. No long-term delayed complications were observed in our patients at a mean follow-up of 3 months. The mean length of hospital stay for inguinal lymphorrhoea was not significantly higher than that for those undergoing reconstructive surgery. Conclusion: Reconstructive surgery improves pain, function, and early postoperative recovery. Application of NPWT is an effective modality for treating inguinal lymphorrhoea. Collaboration with the plastic surgery team is essential in achieving the same for the benefit of such patients.